ALDH1A1 as a Stem Cell Marker and its Correlation with the Clinico-pathological Parameters in Invasive Mammary Carcinoma - ED Hassab El-Naby, Noha; Hashem Mohammed, Maisa; Ahmed, Nagwa Abd El-Sadek (Asian Pacific Journal of Cancer Biology, 2025)
Background: Breast cancer is a major public health concern due to its high incidence worldwide. Globally, it is considered the most common cancer to be diagnosed and one of the main causes for cancer deaths in women. Breast cancer stem cells (BCSCs) are the leading cause of adverse clinical outcomes and resistance to therapeutic agents because of their great capacity for self-renewal and differentiation. Aldehyde dehydrogenase1A1 (ALDH1A1) belongs to the aldehyde dehydrogenase (ALDH) superfamily of enzymes. It is one of the most important markers for cancer stem cells (CSCs). Its expression level in tumor cells is higher than in normal tissues. Recently, it has been widely investigated as a potential prognostic factor and therapeutic target. Objectives: The purpose of this study was to assess the prognostic value of ALDH1A1 expression in invasive mammary carcinoma by correlating its expression to various clinicopathological characteristics and molecular subtypes and highlight the relationship between ALDH1A1 expression and tumor-infiltrating lymphocytes (TILs). Methods: Seventy-two samples of invasive mammary carcinoma were retrieved from the archive of the Pathology Laboratory, Sohag University Hospital; of which 70 were of ductal origin and only 2 were of lobular origin, which were excluded from statistical analysis and discussed separately. Immunohistochemical (IHC) expression of ALDH1A1 was evaluated using an anti-human ALDH1A1 antibody. To elucidate the prognostic value of ALDH1A1 in breast cancer, its expression was statistically correlated with the available clinicopathological data. Results: This study revealed positive ALDH1A1 expression in 54.3% of mammary invasive ductal carcinoma (IDC) specimens. ALDH1A1 up-regulation was significantly positively correlated with poor prognostic indicators, including larger tumor size (p= 0.007), high grade (p= 0.001), advanced stage (p< 0.001), poor Nottingham Prognostic Index (NPI) (p= 0.01), lymphovascular invasion (LVI) (p= 0.03), lymph node metastasis (LNM) (p=0.04), and a triple negative phenotype (p< 0.001). Moreover, we observed that tumors with positive ALDH1A1 expression exhibited higher levels of TILs with a statistically significant correlation (p= 0.001). Conclusion: The current study revealed that ALDH1A1 up-regulation in invasive breast carcinoma is linked to aggressive behavior and different unfavorable prognostic indicators. It could be useful as a promising potential prognostic biomarker, serving as a prospective target for anti-cancer therapy.